2014
DOI: 10.5539/eer.v4n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Carbon Behaviours: What Psychological and Demographic Factors Contribute to Individual Differences in Home Energy Use Reduction and Transportation Mode Decisions?

Abstract: As pressure mounts on countries to reduce carbon emissions, there is increasing interest in understanding what drives "carbon behaviours", in order to inform behavioural change policies. This study examined the impact of psychological and demographic variables, on "carbon behaviours". Secondary data analysis was carried out to investigate the antecedents of residential energy use reduction behaviours and choice of transportation mode for commuting and grocery shopping. Models explained 18.2% and 25.2% of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In terms of awareness and perception of human cause, a nation's wealth and education are greater indicators (Knight, 2016). To promote sustainable behaviour, research has shown that appealing to emotions while developing a nation's climate policy through, for example, marketing/ advertising efforts, can affect the climate change beliefs of individuals (Hall & Allan, 2014;Howell, 2014;Kim & Wolinsky-Nahmias, 2014;Semenza et al, 2008). While the results of the current study demonstrate that beliefs have a significant influence on individual climate change behaviour, the connection between how beliefs turn into behaviour remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of awareness and perception of human cause, a nation's wealth and education are greater indicators (Knight, 2016). To promote sustainable behaviour, research has shown that appealing to emotions while developing a nation's climate policy through, for example, marketing/ advertising efforts, can affect the climate change beliefs of individuals (Hall & Allan, 2014;Howell, 2014;Kim & Wolinsky-Nahmias, 2014;Semenza et al, 2008). While the results of the current study demonstrate that beliefs have a significant influence on individual climate change behaviour, the connection between how beliefs turn into behaviour remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental literacy in ecology dictionary referred to the knowledge of natural systems and ecological concepts, the understanding of environmental issues and the environmental problem-solving with investigation, thinking and communication (Liu and Lin, 2014). As Hall and Allan (2014) pointed out, environmental literacy referred to individual knowledge and attitudes related to the environment and environmental issue, skills and motivation to solve environmental problems, and willingness to maintain the dynamic balance between life quality and environmental quality (Hall and Allan, 2014). Rashid and Asghar (2016) proposed that environmental literacy should focus on responsible environmental behaviors and ecology concepts related to environment and the implied mutual relationship among environments (Rashid and Asghar, 2016).…”
Section: Environmental Ethics and Literacymentioning
confidence: 99%
“…The most useful and concise way to do this was deemed to be the Likert scale as employed by Hall and Allan (2014); as such a 1-5 score was assigned, with 1 illustrating a minor relevance to the topic and 5 showing significant overlap with course material. The benefits of using the Likert scale were considered to be its simplicity of construction, the ease with which participants can read and complete the scoring system and the likelihood of producing a highly reliable scale (Bertram, 2007).…”
Section: Investigating Existing Course Provisionmentioning
confidence: 99%